Aggregative growth of quasi-octahedral iron pyrite mesocrystals in a polyol solution through oriented attachment. Issue 46 (10th October 2016) - Xian, Haiyang; Zhu, Jianxi; Tang, Hongmei; Liang, Xiaoliang; He, Hongping; Xi, Yunfei
Abstract : The growth of iron pyrite mesocrystals includes classical nucleation and growth, aggregative growth through oriented attachment, and Ostwald ripening. Abstract : Uniform iron pyrite mesocrystals were synthesized in a polyol solution. The growth processes of the iron pyrite mesocrystals include classical nucleation and growth, aggregative growth through oriented attachment, and Ostwald ripening. The growth mechanism may improve the controllable synthesis of iron pyrite crystals in terms of size, shape, properties, and potential applications such as electrocatalysis and photoelectrocatalysis.